2014
DOI: 10.4097/kjae.2014.67.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of incidence of intravascular injections during transforaminal epidural steroid injection using different needle types

Abstract: BackgroundInfrequent but serious complications of transforaminal epidural steroid injection (TFESI) occur due to inadvertent intravascular injections. A few studies reported that the different needle types can influence on the occurrences of intravascular incidence in TFESI. This study prospectively evaluated whether short-bevel needle can reduce the incidences of intravascular injection of TFESI compared to long-bevel needles.MethodsFrom March 2013 to December 2013, 239 consecutive patients were enrolled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Although the TF path involves a greater risk for an accidental intravascular injection, this is also possible after an interlaminar injection . Other authors found the incidence of an intravascular pattern for the TF path at the lumbar level between 11.2% and 15.5% and at the cervical level 19.4% . The chance for TF intravascular injection is greater at the S1 level (21.3%) in comparison with the lumbar level (8.1%) …”
Section: Avoidance Of Vascular Injectionmentioning
confidence: 97%
“…Although the TF path involves a greater risk for an accidental intravascular injection, this is also possible after an interlaminar injection . Other authors found the incidence of an intravascular pattern for the TF path at the lumbar level between 11.2% and 15.5% and at the cervical level 19.4% . The chance for TF intravascular injection is greater at the S1 level (21.3%) in comparison with the lumbar level (8.1%) …”
Section: Avoidance Of Vascular Injectionmentioning
confidence: 97%
“…The initial search identified 335 articles in PubMed, 402 in EMBASE, 384 in Web of Science, 335 in MEDLINE complete, and 174 in the Cochrane Library. After the screening of the articles, 25 articles were identified to be associated with intravascular injection, and excluding those related to only one needle type, without transforaminal approach, animal models, review articles, and case reports, three randomized controlled trials and three observational studies were identified for analysis [202122232425]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 shows a flow diagram of the study selection as recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) [27]. All six studies performed epidural injection using the transforaminal approach [202122232425]. Four of the six studies reported data at the lumbosacral level [21232425], and one reported data at the S1 level [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadvertent intravascular injection has been suggested as the most probable mechanism behind serious neurological complications during TFESI [4][5][6]. The incidence of inadvertent intravascular injection during TFESI has been estimated to be 6-26% depending on the level of the injection [7][8][9][10][11][12]. A review of current literature reveals several studies evaluating factors involved in intravascular uptake during TFESI such as needle type, level of injection, injection approach, underlying comorbidities and so on.…”
Section: Introductionmentioning
confidence: 99%